Inclusive speech strategies for Malaysian children with autism - Hassan, Muhamad Hafiz; Wardi, Rainal Hidayat; Shahbuddin, Adib Zakwan Al-Qayyum; Michael, Valerie; Isa, Badrul (Faculty of Art and Design, 2025)
This qualitative study examines the effectiveness of visual-spatial approaches in promoting speech development among children with Autism Spectrum Disorder (ASD) while analysing how cognitive and affective factors mediate communication outcomes. Through semi-structured interviews with eight experienced instructors across Malaysian special education settings, this study examined the implementation experiences with visual support systems, particularly the Picture Exchange Communication System (PECS). Thematic analysis revealed complex relationships between visual-spatial interventions and speech development, mediated by cognitive factors (autism severity, developmental level) and affective factors (motivation, confidence). The findings support an evidence-based framework for inclusive communication interventions aligned with SDG 4, emphasizing individualized approaches in supporting children with ASD.